Exploring new ways of being male: narrative analysis in the building an alternative masculinity - Trujano Ruíz, Patricia (2021)
The expressions of gender are gradually becoming diversified in a contemporary society of profound transformations, giving rise to more inclusive manifestations. Our objective was to explore the processes of construction of an alternative masculine identity of a young university student, analyzing his narratives from the Socioconstructionist theoretical framework through a semi-structured interview. Within his system of meanings, we founded the presence of violence in his childhood and a macho environment that led him to tailor his own personal and relational style with a clear female influence to define an androgynous personality. The pressure of heterocentric discourses was also evident through violence against dissidents to the social order. This work contributes to make visible the processes of construction of different personalities from generic normativity, and emphasizes the need to develop research that gives voice to the social minorities of our time.